2016
DOI: 10.1108/md-10-2015-0444
|View full text |Cite
|
Sign up to set email alerts
|

Putting process on track: empirical research on start-ups’ growth drivers

Abstract: Purpose – The purpose of this paper is to review the literature on the growth drivers of start-up firms from the process perspective. Increasing scholarly attention to the growth of start-up firms has led to a more sophisticated understanding of their drivers. However, the richness of the results is partly offset by both potential and real contradictions in the literature.\ud Design/methodology/approach – In this paper, 233 studies on the growth of start-up firms are reviewed using a process-oriented lens.\ud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 80 publications
(84 reference statements)
0
24
0
Order By: Relevance
“…2. Start-ups (Pugliese et al, 2016) and MSMEs (Nolan & Garavan, 2016) operate to provide value to customers and generate profits for themselves. 3.…”
Section: New Business Venturesmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Start-ups (Pugliese et al, 2016) and MSMEs (Nolan & Garavan, 2016) operate to provide value to customers and generate profits for themselves. 3.…”
Section: New Business Venturesmentioning
confidence: 99%
“…Start-ups have been studied by many researchers across different countries and in different business and market contexts because of the very high potential economic and social value they hold for those countries and contexts (Hillemane et al, 2019; Ojaghi et al, 2019; Pugliese et al, 2016; Tripathi, Seppanen et al, 2018). Yet, there are no accepted definitions of Start-ups (Bortolini et al, 2018; Spender et al, 2017; Zaech & Baldegger, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We consider the response phase of the disaster management life cycle as an unfolding global process of stages and sub-processes rather than just an enumeration of potential activities. The advantage of a processbased approach is that it supports the complex and non-linear explanations about how and why sequences of events occur (Pugliese et al, 2016). As such, our study responds to Neal's call to reexamine empirically and theoretically the issue of disaster phases (Neal, 1997) as well as to the need for a renewed understanding of responding to modern disasters (Lagadec, 2009a;OECD, 2003;Robert & Lajtha, 2002).…”
Section: Disaster Phase Researchmentioning
confidence: 80%
“…Recent research has revealed that a lot of modern disasters have the potential to evolve into 'disasters out of the box' for the intervening EMO-units (De Smet et al, 2014), which should enforce us to rethink the acquired paradigms if we want to be well prepared to deal with future events (Lagadec, 2009a;Robert & Lajtha, 2002). Second, we followed a process-based approach to explain the complex sequence of response events and activities after disaster impact (Pugliese et al, 2016). Our study reveals that the response phase is more than just a set of activities that disaster managers can appeal to in order to stabilize the situation, and to limit injuries, loss of life and damage to property and the environment.…”
Section: The Event Assessment Processmentioning
confidence: 99%
See 1 more Smart Citation